2019
DOI: 10.3920/wmj2018.2384
|View full text |Cite
|
Sign up to set email alerts
|

Combination of microwave and gamma irradiation for reduction of aflatoxin B1 and microbiological contamination in peanuts (Arachis hypogaea L.)

Abstract: Aflatoxin B1 (AFB1) is a natural carcinogen commonly present in food and feed which has deleterious effects on human and animal health. Combination treatment of microwave heating and gamma irradiation has been investigated. Artificially spiked peanuts (Arachis hypogaea L.) were used with a concentration of 300 μg/kg of AFB1 to evaluate the treatment efficacy. Qualitative and quantitative analysis of AFB1 was carried out by one dimensional thin layer chromatography and enzyme-linked immune-sorbent assay (ELISA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Dehulling removed 92% of the initial aflatoxin content from corn kernel Siwela et al, 2005 Aflatoxin residuals in corn after crushing and dehulling was almost negligible Fandohan et al, 2005 Dehulling decreased AF content of corn by 5.5-70% Mutungi et al, 2008 Dehulling and whitening of rice kernel resulted 96% decrease in AF content in polished broken grains and 79% in polished whole kernels Castells et al, 2007 Dehulling of corn kernels resulted in 88 and 92% reduction in AFB 1 and AFB 2 levels Matumba et al, 2015 Reduction, destruction Pulsed light treatment (0.52 J/cm 2 /pulse in spectrum of 100-1100 nm with a xenon flash lamp) resulted 75-90% decreases in AFB 1 and AFB 2 contents of rice and rice bran Wang et al, 2016 6 and 10 kGy gamma irradiation doses resulted 90 and 95% reduction in AFB 1 , respectively Serra et al, 2018 In peanuts, 5-9 kGy gamma irradiation doses result 20-43% decrease in aflatoxins, microwave radiation at 360, 480, and 600 W resulted 59-67% decrease, combined treatments have higher than 95% efficiency Patil et al, 2019 Destruction by cold plasma Hazelnuts, peanuts, and pistachio nuts treated with air gases plasma for 20 min resulted 50% decrease in total aflatoxins, SF 6 plasma application resulted only 20%reduction Basaran et al, 2008 Atmospheric plasma generated with 400-1150 W power for 1-12 min resulted 46-71% decrease in AFB 1 in peanuts Siciliano et al, 2016 High voltage atmospheric cold plasma applied for 1 and 10 min resulted 62 and 82% reduction in AFs levels of corn.…”
Section: Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Dehulling removed 92% of the initial aflatoxin content from corn kernel Siwela et al, 2005 Aflatoxin residuals in corn after crushing and dehulling was almost negligible Fandohan et al, 2005 Dehulling decreased AF content of corn by 5.5-70% Mutungi et al, 2008 Dehulling and whitening of rice kernel resulted 96% decrease in AF content in polished broken grains and 79% in polished whole kernels Castells et al, 2007 Dehulling of corn kernels resulted in 88 and 92% reduction in AFB 1 and AFB 2 levels Matumba et al, 2015 Reduction, destruction Pulsed light treatment (0.52 J/cm 2 /pulse in spectrum of 100-1100 nm with a xenon flash lamp) resulted 75-90% decreases in AFB 1 and AFB 2 contents of rice and rice bran Wang et al, 2016 6 and 10 kGy gamma irradiation doses resulted 90 and 95% reduction in AFB 1 , respectively Serra et al, 2018 In peanuts, 5-9 kGy gamma irradiation doses result 20-43% decrease in aflatoxins, microwave radiation at 360, 480, and 600 W resulted 59-67% decrease, combined treatments have higher than 95% efficiency Patil et al, 2019 Destruction by cold plasma Hazelnuts, peanuts, and pistachio nuts treated with air gases plasma for 20 min resulted 50% decrease in total aflatoxins, SF 6 plasma application resulted only 20%reduction Basaran et al, 2008 Atmospheric plasma generated with 400-1150 W power for 1-12 min resulted 46-71% decrease in AFB 1 in peanuts Siciliano et al, 2016 High voltage atmospheric cold plasma applied for 1 and 10 min resulted 62 and 82% reduction in AFs levels of corn.…”
Section: Removalmentioning
confidence: 99%
“…Several radiation sources have been evaluated thus far and many of them were found to be effective. For example, the advantageous effects of UV in liquid phase (Patras et al, 2017), gamma irradiation in corn (Markov et al, 2015;Serra et al, 2018), in other cereal kernels (Mohamed et al, 2015), in peanuts (Patil et al, 2019) and in poultry feed (Herzallah et al, 2008) have been reported in a number of publications. Direct sunlight was also effective in aflatoxin reduction in poultry feed (Herzallah et al, 2008) and, in addition to exposures to direct light, the applicability of pulsed light has also been tested and evaluated, and it has already been employed in new decontamination technologies (Moreau et al, 2013).…”
Section: Shi Et Al 2017mentioning
confidence: 99%
“…In a study on naturally contaminated maize samples, Markov et al [ 15 ] reported that gamma irradiation at a 10 KGy-dose reduced AFB 1 by 94.5 %. Meanwhile, Patil et al [ 16 ] indicated that AFB 1 was reduced by 20–43% in artificially spiked peanuts using gamma irradiation (5–9 KGy). On the other hand, other studies showed conflicting results depending on the food matrix and the experimental setup [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, meanwhile, thermal treatments, sorting, and dehulling may decrease other food risks including microbiological contaminations, pesticide residues, and toxic elements [143][144][145], they can also result in significant losses in nutrients [91,143]. Therefore, holistic approaches should be used to test the toxicological and nutritional consequences of treatments and the effects of sample matrices, since the efficiencies of physical methods are strongly dependent on the materials to be decontaminated and the application conditions [34,41,49,58]. Modern mathematical methods are available for multi-purpose optimization of processing parameters, taking into account the relationships existing between structure, composition, shelf-life, and safety [146,147].…”
Section: Potentials and Challenges Of Upscaling Experimental Detoxifying Methodsmentioning
confidence: 99%
“…Higher than the 10 kGy dose was found to be useful in AFB1 reduction in soybean [ 57 ]. Lower values for AF decreases (20–43% decrease for 5–9 kGy doses) were reported in peanuts and found that low power microwave heating was much more effective (59–67% decrease at 360, 480, and 600 W), although the combination of the two irradiations resulted in a higher than 95% reduction [ 58 ]. When the effects of 5–25 kGy dose gamma irradiations on the AF content of artificially contaminated mixed poultry feed were examined, lower efficiency, 5–43% decrease in total aflatoxin and aflatoxin B1 content was found [ 53 ].…”
Section: Reduction In Aflatoxins In Feed and Foodmentioning
confidence: 99%